Differential vulnerability: disentangling the effects of state dependence and population heterogeneity on repeat victimization - Clay-Warner, Jody (Criminal justice and behavior, 2016)
It is well established that victimization is associated with increased risk of future victimization. According to state dependence arguments, this occurs because the victimization event changes either the individual or the social environment in ways that elevate risk. In contrast, the population heterogeneity perspective argues that the association between victimization events is spurious. Empirical research finds that state dependence and population heterogeneity jointly contribute to risk of repeat victimization, but research has not been able to specify the nature of the relationship between state dependence, population heterogeneity, and repeat victimization risk. Here, we propose that state dependence processes vary across levels of underlying propensity for victimization. Using propensity score matching with longitudinal data from the National Crime Victimization Survey, we find that state dependence effects operate differently depending upon one?s underlying risk of victimization and that the pattern of these effects differ for property and violent victimization.